IMPLEMENTASI PROGRAM SISTEM INFORMASI AKADEMIK SIAKAD DI STKIP PGRI BANGKALAN - Agoeng Koerniawan SA (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this study was to determine the role of academic information systems in improving the quality of higher education implementation in PGRI STKIP Bangkalan, and the extent to which the policies of implementing higher education before and after the use of information systems and how satisfaction is felt by students towards academic information systems at STKIP PGRI Bangkalan, named STKIP PGRI Bangkalan’s Siakad.The study was conducted by conducting a survey of users of the internet-based academic information system (Siakad STKIP PGRI Bangkalan), namely lecturers, students, and employees with the method of observation and conducting in-depth interviews to obtain as much information as possible from all respondents/informants. The number of informants was 5 people consisting of the chairman of STKIP PGRI Bangkalan, Vice Chairman I, Head of BAAK, and two students who had experience in their respective fields of work knew deeply and had many roles in the process of using information systems.Based on the results of the study, it was shown that with the use of the information system/ STKIP PGRI Bangkalan’s Siakad which is one of the facilities for the smooth activities of the teaching and learning process, it proved to provide convenience, many benefits, and benefits that greatly support the duties of serving lecturers, students and outsiders requiring. This is evidenced by the support of lecturers and students, capacity, namely the ability of employees to process data and value, namely the benefits felt by lecturers, employees, and students as well as outside parties in need.